The Reliability of Two Different Laser Wavelengths in Inducing Bone Healing Around Dental Implants: Comparative Clinical Trial - Zahraa A. Alameeri*,; Hussein A. Jawad, (Iraqi Journal of Laser, 2023)
Background/purpose: Dental implantology involves different treatments that have been used in conjunction with dental implant surgery to increase implant stability and bone regeneration process. Photobiomodulation( PBM) can be one of these techniques. The objective of this study was to evaluate the bone density around implants. Materials and methods: in this study, 10 individuals had 20 implants inserted in the posterior of their mandibles. each patient received two implants the left side served as the control whereas the right side served as the study group with a diode laser (same patients). measurements were made for each implant. Measurements were obtained using cone-beam computed tomography (CBCT). Results: Cone beam computed tomography (CBCT) analysis found statistically significant quotient differences between the study groups were discovered. (P =